Algorithmic Market Transformation - Lina Marlina (Manexia: Journal of Business, Management, and Creative Economy, 2026)
This editorial introduces a collection of conceptual articles examining how algorithmic infrastructures are reshaping the foundations of digital markets. Rather than functioning merely as operational tools, artificial intelligence increasingly acts as a structural coordination mechanism influencing market architecture, organizational boundaries, demand formation, pricing legitimacy, and productivity dynamics. Together, the contributions in this issue highlight how algorithmic governance redistributes control, restructures competitive interaction, and generates new forms of performance divergence within platform-mediated digital ecosystems.